La vigencia de la ley transitoria de municipalidades de 1857 y su naturaleza declarativa de interés nacional: a propósito del caso del centro poblado de Iquicha - Villalobos Villalobos, Vicente Brayan (2022)
During the provisional government of marshal Ramón Castilla (1855-1858), the National Convention installed in 1855, promulgated the Transitory Law of Municipalities on January 2, 1857. This law provided for the creation of municipalities in 691 districts included in the then existing provinces and departments, among which the district of Iquicha, located in the province of Huanta, region of Ayacucho, is mentioned. However, due to socio-political events and conflicts that affected the cohesion, life and development of this community, the demarcation action was not carried out. Already in 2022, the author of this work was contacted with some representatives of the Iquichana community –resettled in a perfectly determinable high Andean area as they were told– to take some legal action aimed at demanding the Peruvian State implement the respective district.Thus, this text derives from the thesis that the author raised in a compliance process initiated against the Department of Demarcation and Territorial Organization of the Presidency of the Council of Ministers, due to the reluctance of this body to execute the aforementioned law of municipalities (material inactivity of the Public Administration). To achieve this objective, the author claims that the law in question has a declaratory nature of national interest, despite not containing the linguistic statement used by the current legislative technique for the drafting of declarative laws. During the development of his reasoning and argumentation, he addresses several issues closely linked to the controversy, such as the validity and effectiveness of the norms, the methods of legal interpretation, the material content of the declarative laws, the collision between the constitutional precedent “Villanueva Valverde” and the new regulation of the compliance process, among other concepts and legal categories. Likewise, to contextualize the case and highlight the social problems of the Iquichano people, it integrates some sociological and historical studies of this community.